2012
DOI: 10.1161/hypertensionaha.111.184986
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Influence of Angiotensin Type 2 Receptor Stimulation on Renal Function

Abstract: Abstract-The renin-angiotensin system is a powerful regulator of arterial pressure and body fluid volume. Increasing evidence suggests that the angiotensin type 2 receptor (AT 2 R), which mediates the vasodilatory and natriuretic actions of angiotensin peptides, is enhanced in females and may, therefore, represent an innovative therapeutic target. We investigated the therapeutic potential of direct AT 2 R stimulation on renal function in 11-to 12-week-old anesthetized male and female Sprague-Dawley rats. Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
84
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 25 publications
17
84
2
Order By: Relevance
“…7 This observation of a sex-specific renal vascular response to C21 in the present study is consistent with our previous observations in rodents that AT 2 R plays a greater functional role in female than in male renal vasculature, providing protection against the vasoconstrictor effects of AngII. 5,6,8 Furthermore, our data support the notion that differences in the renal response to C21 between male and female SHRs is attributable to sex differences in renal AT 2 R expression. We observed significantly greater basal AT 2 R mRNA expression in the kidneys of female SHRs as compared with male SHRs, in agreement with the previous findings of Silva-Antonialli et al 2 In addition, although we observed significantly greater renal angiotensin type 1a receptor expression in female SHRs as compared with their male counterparts, the relative AT 2 R-to-AT 1 R ratio was much greater in female than in male SHRs, although such sex differences in basal renal AT 1 R or AT 2 R mRNA expression are not always reported.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…7 This observation of a sex-specific renal vascular response to C21 in the present study is consistent with our previous observations in rodents that AT 2 R plays a greater functional role in female than in male renal vasculature, providing protection against the vasoconstrictor effects of AngII. 5,6,8 Furthermore, our data support the notion that differences in the renal response to C21 between male and female SHRs is attributable to sex differences in renal AT 2 R expression. We observed significantly greater basal AT 2 R mRNA expression in the kidneys of female SHRs as compared with male SHRs, in agreement with the previous findings of Silva-Antonialli et al 2 In addition, although we observed significantly greater renal angiotensin type 1a receptor expression in female SHRs as compared with their male counterparts, the relative AT 2 R-to-AT 1 R ratio was much greater in female than in male SHRs, although such sex differences in basal renal AT 1 R or AT 2 R mRNA expression are not always reported.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is somewhat surprising given that we and others have previously reported significant natriuretic effects of AT 2 R stimulation alone in numerous male rodent models, including normotensive Sprague-Dawley rats, uninephrectomized rats, and obese Zucker rats. 6,[13][14][15] This finding suggests that the lesser renal AT 2 R expression we and others have identified in male versus female SHRs may be responsible for the lack of natriuretic response of male SHRs to C21 in the present study.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations